Technology Acceptance Level (TAL): A human-centred metric for evaluating trustworthy artificial intelligence in agriculture - Andreas Holzinger; Stefan Schweng; Kevin Mallinger; A. Min Tjoa; Peter Riegler-Nurscher; Mayuri Mehta (Computers and Electronics in Agriculture, 2026)

In silico, in vitro antimicrobial and synergistic potential of Cymbopogon citratus (DC.) essential oil - Deeksha Salaria; Rajan Rolta; Amit Raj Sharma; Olatomide A. Fadare; Jyoti Mehta (South African Journal of Botany, 2026)

Effects of personality traits and context congruency on participant engagement in traditional central location tests and congruent versus incongruent digital immersive environments during affective product testing - Annu Mehta; Caroline Giezenaar; A. Jonathan R. Godfrey; Rebekah E. Orr; Simone Poggesi; Meika Foster; Joanne Hort (Food Quality and Preference, 2026)

Electrospun Nanofibers Based Locoregional Chemotherapy Targeting Squamous Cell Carcinomas: Recent Investigation Through In Vitro and In Vivo Activity - Anam Sami; Kartik Hariharan; Tejal. A. Mehta (Journal of Pharmaceutical Innovation, 2026)

Transcriptional Scenario of Altered Glycosylation in HPV-Associated Cervical Cancer - Ashi R. Thobias; Kinjal A. Patel; Kruti A. Mehta; Bijal M. Patel; Jayendra B. Patel; Prabhudas S. Patel (Indian Journal of Clinical Biochemistry, 2026)

Photocatalytic degradation of methylene red dye using biosynthesized silica coated semiconductor photocatalyst - M A Ashwini; Yashneeti Mehta; Anita Gupta; Kumar Rakesh Ranjan; Maumita Das Mukherjee; Parul Khurana; Sheenam Thatai (Next Research, 2026)

Morays need to get a grip!—The California moray (Gymnothorax mordax) uses its body and the environment for leverage during feeding - Maya M. McElfish; Avery A. McDaniel; Sacha E. O’Connor; August D. Robinette; Rita S. Mehta (Environmental Biology of Fishes, 2026)
Many predatory fishes hunt and feed in structurally complex environments making their feeding behaviors challenging to observe. We designed a transparent microhabitat to document how the California moray ( Gymnothorax mordax ) uses its elongated body to apply leverage during crevice foraging within the rocky reef. To generate leverage, these predatory fish use complex behaviors to extract prey from tight spaces. Morays form anchors by using the body in combination with the surrounding environment to maintain position. We demonstrate that morays can brace themselves internally within the crevice by strategically pushing against the interior surfaces, forming sinusoidal waves with their body, creating one to four bracing anchor points. More often, morays anchor themselves by extending their tail out of the crevice and wrapping around the crevice edge to facilitate pulling. In addition, we observed morays using leverage through knot tying, using three distinct patterns of knots with the simple overhand knot observed most frequently, which can occur within and outside of crevices. Our observations highlight the tactical behavioral diversity these cryptic predators use to overcome physical constraints and forage successfully in spatially complex environments.

The GPR139 agonist TAK-041 produces time-dependent alterations to cerebral blood flow and reward system function in patients with schizophrenia: a randomised placebo-controlled trial - Peter C. T. Hawkins; Adam J. Schwarz; James M. Stone; Fiona Pepper; James Gilleen; Sam Gijsen; Ndabezinhle Mazibuko; Dimitrios Arkilo; Wei Yin; Jingtao Wu; Polyna Khudyakov; Rhett Behrje; et al. (Psychopharmacology, 2026)
The negative and cognitive symptoms of schizophrenia are predictive of quality of life and functional recovery, but there are no approved drug options that target these symptoms directly. TAK-041 (also known as NBI-1065846) is a selective and potent small-molecule agonist of GPR139, an orphan G-protein-coupled receptor, which has been shown to reverse deficits related to negative and cognitive symptoms in animal models. In this proof-of-activity study to evaluate the effects of TAK-041 on motivational anhedonia, 23 adults with schizophrenia experiencing moderate to severe negative symptoms were administered a single 40 mg or 160 mg dose of TAK-041 in a randomised, double-blind, placebo-controlled, two-period crossover design. Functional magnetic resonance imaging (fMRI) assessment of reward function (monetary incentive delay [MID] task) and cerebral blood flow (CBF), as well as cognitive assessment with the Brief Assessment of Cognition in Schizophrenia (BACS) tool, were performed 3 h post dose and after 14 days. There was no significant effect of TAK-041 compared with placebo on BACS score at either timepoint. There was also no significant effect of TAK-041 on MID fMRI at day 1; however, at day 14, TAK-041 produced an increase in reward anticipatory activity in the ventral striatum compared with placebo. There was a significant decrease in CBF throughout the brain at day 1 that then reversed, resulting in a relative increase at day 14, compared with placebo. At day 14 there was a significant interaction between drug and CBF on reward anticipatory BOLD, indicating that drug-related changes to CBF may partially contribute to the observed BOLD effects (although the main effect of drug on the BOLD signal remained significant after including CBF as a covariate in the model). These data indicate that TAK-041 produces detectable changes in both CBF and reward task related fMRI signal in brain regions linked with symptoms and treatment response in schizophrenia. IND Number: 130074| EudraCT Number: 2017-001084-20| Clincaltrails.gov registry: NCT03319953.

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Design of Experiments-Based RP-HPLC Bioanalytical Method Development and Validation for Ticagrelor Quantification in Rat Plasma with Pharmacokinetic Application - Mariyambibi A. Mandarawala; Ashok N. Mahajan; Shaileshkumar K. Koradia; Moinuddin M. Soniwala; Sohel A. Punasiya; Dimal A. Shah; Falgun A. Mehta (Journal of Pharmaceutical Innovation, 2026)

Physiologically based pharmacokinetic modeling of oseltamivir in pregnant rhesus macaques to inform clinical dosing across trimesters - Darshan Mehta; Kiara Fairman; Miao Li; Jeffrey Fisher; Frederick A. Beland; Gonçalo Gamboa da Costa; Annie Lumen (Regulatory Toxicology and Pharmacology, 2026)

Exploring the association of personal factors with affective responses to plant-based meat alternatives with consideration of their perceived similarity to meat. - Caroline Giezenaar; Annu Mehta; Rebekah E. Orr; A. Jonathan R. Godfrey; Meika Foster; Joanne Hort (Food Quality and Preference, 2025)

Genomics-assisted stacking of waxy1, opaque2, and crtRB1 genes for enhancing amylopectin in biofortified maize for industrial utilization and nutritional security - Subhra J. Mishra; Firoz Hossain; Rajkumar U. Zunjare; Rashmi Chhabra; Ashvinkumar Katral; Ikkurti Gopinath; Vinay Bhatt; Govinda Rai Sarma; Zahirul A. Talukder; Ravindra K. Kasana; Elangbam L. Devi; Konsam Sarika; et al. (Functional & Integrative Genomics, 2025)

Insights from degradation studies of alpha mangostin from Garcinia mangostana : key findings - Pratixha M. Palkar; Shital B. Palghadmal; Shankar S. Mane; Priti A. Darne; Shankar V. Vidhate; Nisha A. Mehta; Sriram Padmanabhan (Natural Product Research, 2025)

Transforming the Evaluation of Agrochemicals: A Conceptual Model - Bhuller Yadvinder; Bishop Patricia; Cope Rhian; Corvaro Marco; Richard A. Currie; Gina M. Hilton; Mehta Jyotigna; Puglisi Raechel; Douglas C. Wolf; Sandrine E. Deglin (Regulatory Toxicology and Pharmacology, 2025)

Getting over it? A proteomic analysis of mechanisms driving multigenerational acclimation to organic ultraviolet filters in Daphnia magna - Aaron Boyd; Christina Lummer; Devang Mehta; R. Glen Uhrig; Tamzin A. Blewett (Environmental Pollution, 2025)

A case study on the intrusions of the dust and smoke aerosols and their direct radiative impacts on the surface heating - P. Prasad; A. Aravindhavel; Sanjay Kumar Mehta; Purushotham Pooja; Sachin Philip Kakkanattu; Y. Jaya Rao; Thara Prabhakaran (Air Quality, Atmosphere & Health, 2025)

Gut microbiome-targeted therapies and bone health across the lifespan: a scoping review - Maahika Mehta; Erin Hodgson; Raylene A. Reimer; Leigh Gabel (Critical Reviews in Food Science and Nutrition, 2025)

P28-40 Potential MoA for rare fetal eye findings in rabbit prenatal developmental toxicity studies with TFA - A. Hüser; C. Glatt; I. Fegert; J. Mehta; L. Bertomeu; M. Temerowski; M. Schutte; S. Melching-Kollmuss; R. Bartlett (Toxicology Letters, 2025)

P24-23 Key Agronomic and Safety Characteristics (Key ASCs) and why they matter to improve safety and reduce reliance on animal testing for agricultural solutions - M. Corvaro; M. Battalora; L. Bertomeu; S. Ellis; I. Fegert; J.-C. Garcin; S. Kan-King-Yu; T. Mehta; S. Nadzialek; B. Neumann; P. Rawlinson; U. Rooni; et al. (Toxicology Letters, 2025)

Brazilian Cerrado soil microbiota captures the impacts of agricultural practices and unveils a promising ecosystem for antimicrobial peptide discovery - F.T.P.K. Távora; R.S. Oliveira; T.B. Rios; D.G. Ribeiro; L.M. Souza; F.B. Reis Junior; W. Fontes; M.S. Castro; M.V. Sousa; O.L. Franco; A. Mehta (Applied Soil Ecology, 2025)

Opioidergic modulation of monetary incentive delay fMRI responses - Samuel Turton; Peter C.T. Hawkins; Christopher Muller-Pollard; Evangelos Zois; Patricia Conrod; Fernando Zelaya; Mitul A. Mehta (Psychopharmacology, 2025)
Rationale It is hypothesised that modulation of striatal dopaminergic signalling plays a key role in the rewarding effects of opioids. The monetary incentive delay (MID) task is a functional magnetic resonance imaging (fMRI) paradigm used to investigate striatal responses, which may reflect striatal dopamine release, during the anticipation of a financial reward. Objectives We hypothesised that fentanyl would modulate striatal MID task Blood Oxygenation Level Dependent (BOLD) responses, reflecting opioidergic modulation of striatal dopaminergic signalling. Methods 24 right-handed males who undertook four MRI scanning sessions, during which they completed an MID task 15 min after receiving an intravenous infusion of either one of two doses of fentanyl (50 µg/70kg), naloxone (400 µg) or placebo (saline 0.9%), were included in the analyses. End tidal CO 2 data were collected to control for respiratory depression. Results We demonstrated fentanyl induced increases in MID task reward and loss anticipation BOLD compared with placebo and naloxone in both region of interest (ROI) and whole brain analyses. These results were in cortical regions including the lingual gyrus, precuneus, posterior cingulate and frontal pole rather than the striatum. Conclusions Our results show the primary effects of fentanyl on MID anticipation BOLD in regions associated with the preparation of a motor response to a salient visual cue, rather than in regions typically associated with reward processing such as the striatum. This suggests that opioid agonists do not affect striatal activation during the MID task. Tasks using naturalistic rewards, for example feeding, sex or social contact which induce endogenous opioid signalling, may be more appropriate to probe the effects of fentanyl on reward processing. These results are from male participants’ data and therefore may not be generalisable to female participants.

Development of a 3D Brain Model to Study Sex-Specific Neuroinflammation After Hemorrhagic Stroke - Rezwanul Islam; Hadi Hasan Choudhary; Hritik Mehta; Feng Zhang; Tudor G. Jovin; Khalid A. Hanafy (Translational Stroke Research, 2025)
Subarachnoid hemorrhage (SAH) accounts for 5% of stroke, with women having a decreased inflammatory response compared to men; however, this mechanism has yet to be identified. One hurdle in SAH research is the lack of human brain models. Studies in murine models are helpful, but human models should be used in conjunction for improved translatability. These observations lead us to develop a 3D system to study the sex-specific microglial and neuroglial function in a novel in vitro human SAH model and compare it to our validated in vivo SAH model. Our lab has developed a 3D, membrane-based in vitro cell culture system with human astrocytes, microglia, and neurons from both sexes. The 3D cultures were incubated with male and female cerebrospinal fluid from SAH patients in the Neuro-ICU. Furthermore, microglial morphology, erythrophagocytosis, microglial inflammatory cytokine production, and neuronal apoptosis were studied and compared with our murine SAH models. The human 3D system demonstrated intercellular interactions and proportions of the three cell types similar to the adult human brain. In vitro and in vivo models of SAH showed concordance in male microglia being more inflammatory than females via morphology and flow cytometry. On the contrary, both in vitro and in vivo models revealed that female microglia were more phagocytic and less prone to damaging neurons than males. One possible explanation for the increased phagocytic ability of female microglia was the increased expression of CD206 and MerTK. Our in vitro, human, 3D cell culture SAH model showed similar results to our in vivo murine SAH model with respect to microglial morphology, inflammation, and phagocytosis when comparing the sexes. A human 3D brain model of SAH may be a useful adjunct to murine models to improve translation to SAH patients.

TRPV4 Channel in Neurological Disease: from Molecular Mechanisms to Therapeutic Potential - Feng Zhang; Hritik Mehta; Hadi Hasan Choudhary; Rezwanul Islam; Khalid A. Hanafy (Molecular Neurobiology, 2025)
Transient Receptor Potential Vanilloid 4 (TRPV4) is a non-selective cation channel with pivotal roles in various physiological processes, including osmosensitivity, mechanosensation, neuronal development, vascular tone regulation, and bone homeostasis in human bodies. Recent studies have made significant progress in understanding the structure and functional role of TRPV4, shedding light on its involvement in pathological processes, particularly in the realm of neurological diseases. Here, we aim to provide a comprehensive exploration of the multifaceted contributions of TRPV4 to neurological diseases, spanning its intricate molecular mechanisms to its potential as a target for therapeutic interventions. We delve into the structural and functional attributes of TRPV4, scrutinize its expression profile, and elucidate the possible mechanisms through which it participates in the pathogenesis of neurological disorders. Furthermore, we discussed recent years’ progress in therapeutic strategies aimed at harnessing TRPV4 for the treatment of these diseases. These insights will provide a basis for understanding and designing modality-specific pharmacological agents to treat TRPV4-associated disorders.

Polymeric polyamine: a systematic study on synthesis, characterisation and its application for removal of reactive dye - A. Kumar; Y. Thakare; V. K. Rathore; M. Chakraborty; H. Mehta (International Journal of Environmental Science and Technology, 2025)

Trace elements and metal nanoparticles: mechanistic approaches to mitigating chemotherapy-induced toxicity—a review of literature evidence - Ademola C. Famurewa; Mina Y. George; Cletus A. Ukwubile; Sachindra Kumar; Mehta V. Kamal; Vijetha S. Belle; Eman M. Othman; Sreedhara Ranganath K. Pai (BioMetals, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Atmospheric boundary layer height over a rain-shadow region: An intercomparison of multi-observations and model simulations - P Prasad; A. Aravindhavel; K. Gayatri; Sanjay Kumar Mehta; Y. Jaya Rao; Purushotham Pooja; Sachin Philip Kakkanattu; Raman Solanki; Abhishek Gupta; Shivdas Bankar; Shivsai Dixit; Thara Prabhakaran (Atmospheric Research, 2024)

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

Development of an Experimental Model of Vasculitis Using Ovalbumin Lipopolysaccharide in Rats - Vandana R. Thakur; Anita A. Mehta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Investigating impacts of the mycothiazole chemotype as a chemical probe for the study of mitochondrial function and aging - Naibedya Dutta; Joe A. Gerke; Sofia F. Odron; Joseph D. Morris; Adam Hruby; Juri Kim; Toni Castro Torres; Sarah J. Shemtov; Jacqueline G. Clarke; Michelle C. Chang; Hooriya Shaghasi; Marissa N. Ray; et al. (GeroScience, 2024)
Small molecule inhibitors of the mitochondrial electron transport chain (ETC) hold significant promise to provide valuable insights to the field of mitochondrial research and aging biology. In this study, we investigated two molecules: mycothiazole (MTZ) - from the marine sponge C. mycofijiensis and its more stable semisynthetic analog 8- O -acetylmycothiazole (8-OAc) as potent and selective chemical probes based on their high efficiency to inhibit ETC complex I function. Similar to rotenone (Rote), MTZ, a newly employed ETC complex I inhibitor, exhibited higher cytotoxicity against cancer cell lines compared to certain non-cancer cell lines. Interestingly, 8-OAc demonstrated greater selectivity for cancer cells when compared to both MTZ and Rote, which has promising potential for anticancer therapeutic development. Furthermore, in vivo experiments with these small molecules utilizing a C. elegans model demonstrate their unexplored potential to investigate aging studies. We observed that both molecules have the ability to induce a mitochondria-specific unfolded protein response (UPR MT ) pathway, that extends lifespan of worms when applied in their adult stage. We also found that these two molecules employ different pathways to extend lifespan in worms. Whereas MTZ utilizes the transcription factors ATFS-1 and HSF1, which are involved in the UPR MT and heat shock response (HSR) pathways respectively, 8-OAc only required HSF1 and not ATFS-1 to mediate its effects. This observation underscores the value of applying stable, potent, and selective next generation chemical probes to elucidate an important insight into the functional roles of various protein subunits of ETC complexes and their regulatory mechanisms associated with aging. Graphical Abstract

Predictive active control of building structures using LQR and artificial intelligence - Nirmal S. Mehta; Vishisht Bhaiya; K. A. Patel; Ehsan Noroozinejad Farsangi (Earthquake Engineering and Engineering Vibration, 2024)

A review of solar still technology: solution for water scarcity - A. Chorghe; A. Dhavale; V. Mehta; P. Rao; N. Patel; A. Priyam (International Journal of Environmental Science and Technology, 2024)

Modeling of uncertainty in the estimation of hydrograph components in conjunction with the SUFI-2 optimization algorithm by using multiple objective functions - Shashikant Verma; Mani Kant Verma; A. D. Prasad; Darshan J. Mehta; Md. Nazrul Islam (Modeling Earth Systems and Environment, 2024)

Chitosan scaffolds: Expanding horizons in biomedical applications - Amol D. Gholap; Satish Rojekar; Harshad S. Kapare; Nikhar Vishwakarma; Sarjana Raikwar; Atul Garkal; Tejal A. Mehta; Harsh Jadhav; Mahendra Kumar Prajapati; Uday Annapure (Carbohydrate Polymers, 2024)

Association between household cleaning product exposure in infancy and development of recurrent wheeze and asthma - Isis F. Baroni; Geneva D. Mehta; Ashley F. Sullivan; Carlos A. Camargo; Orianne Dumas (International Archives of Occupational and Environmental Health, 2023)

Spatio-temporal Variations in Air Pollution During the Lockdown of COVID-19 in Delhi: A GIS Approach - S. H. Arshad Peer Mohamed; Manu Mehta; Luvkesh Attri; B. A. Bhargavi; Gaurish Singhal (Aerosol Science and Engineering, 2023)

Minute level smartphone derived exposure to greenness and consumer wearable derived physical activity in a cohort of US women - Grete E. Wilt; Charlotte J. Roscoe; Cindy R. Hu; Unnati V. Mehta; Brent A. Coull; Jaime E. Hart; Steven Gortmaker; Francine Laden; Peter James (Environmental Research, 2023)

Exposure considerations in human safety assessment: Report from an EPAA Partners’ Forum - Mark T.D. Cronin; Nicholas Ball; Sonja Beken; Hans Bender; Ofelia Bercaru; Laura Caneva; Marco Corvaro; Richard A. Currie; Jeffrey L. Dawson; Paul Desert; Sylvia E. Escher; Antonio Franco; et al. (Regulatory Toxicology and Pharmacology, 2023)

Genetic analysis for semen quality traits in buffalo bulls - Devender Kumar; J. S. Mehta; A. Jerome; Pradeep Kumar; D. Kumar; B Shivani; C. S. Patil; Renu Bala; Nisha Verma; Satish Nain; R. K. Sharma; Pawan Singh (Tropical Animal Health and Production, 2023)

Single-dose effects of methylphenidate and atomoxetine on functional connectivity during an n-back task in boys with ADHD - Olivia S. Kowalczyk; Ana I. Cubillo; Marion Criaud; Vincent Giampietro; Owen G. O’Daly; Mitul A. Mehta; Katya Rubia (Psychopharmacology, 2023)
Rationale Working memory deficits and associated neurofunctional abnormalities are frequently reported in attention-deficit/hyperactivity disorder (ADHD). Methylphenidate and atomoxetine improve working memory performance and increase activation of regions under-functioning in ADHD. Additionally, methylphenidate has been observed to modulate functional networks involved in working memory. No research, however, has examined the effects of atomoxetine or compared the two drugs. Objectives This study aimed to test methylphenidate and atomoxetine effects on functional connectivity during working memory in boys with ADHD. Methods We tested comparative effects of methylphenidate and atomoxetine on functional connectivity during the n-back task in 19 medication-naïve boys with ADHD (10–15 years old) relative to placebo and assessed potential normalisation effects of brain dysfunctions under placebo relative to 20 age-matched neurotypical boys. Patients were scanned in a randomised, double-blind, cross-over design under single doses of methylphenidate, atomoxetine, and placebo. Controls were scanned once, unmedicated. Results Patients under placebo showed abnormally increased connectivity between right superior parietal gyrus (rSPG) and left central operculum/insula. This hyperconnectivity was not observed when patients were under methylphenidate or atomoxetine. Furthermore, under methylphenidate, patients showed increased connectivity relative to controls between right middle frontal gyrus (rMFG) and cingulo-temporo-parietal and striato-thalamic regions, and between rSPG and cingulo-parietal areas. Interrogating these networks within patients revealed increased connectivity between both rMFG and rSPG and right supramarginal gyrus under methylphenidate relative to placebo. Nonetheless, no differences across drug conditions were observed within patients at whole brain level. No drug effects on performance were observed. Conclusions This study shows shared modulating effects of methylphenidate and atomoxetine on parieto-insular connectivity but exclusive effects of methylphenidate on connectivity increases in fronto-temporo-parietal and fronto-striato-thalamic networks in ADHD.

Endoscopic and chemopreventive management of familial adenomatous polyposis syndrome - J. K. Stone; N. A. Mehta; H. Singh; W. El-Matary; C. N. Bernstein (Familial Cancer, 2023)

P22-27: Toxicity of 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitors: converging evidence from in vivo and a new approach method invitrothat mouse is the most relevant test species - G. Semino Beninel; C. Strupp; J. Mehta; T. Holmes; J.-C. Garcin; M. Frericks; E. Bianchi; K. Sasaki; J. Botham; A. Charlton; S. Nadzialek (Toxicology Letters, 2023)

Ajay Kumar Parida (1963–2022), an eminent plant biotechnologist with a passion for mangrove biology - Gayatri Venkataraman; M. Parani; Rajeeb Swain; Seema Pradhan; S. N. Raina; A. Gopalakrishnan; Sivaprakash Ramalingam; Suja George; Jithesh M.N.; Praseetha Kizhakkedath; Preeti Angela Mehta; G. N. Hariharan (Physiology and Molecular Biology of Plants, 2023)

Impact of monsoon season rainfall spells on the ecosystem carbon exchanges of Himalayan Chir-Pine and Banj-Oak-dominated forests: a comparative assessment - Priyanka Lohani; Sandipan Mukherjee; K. Chandra Sekar; Pooja Mehta; Kireet Kumar; A. P. Dimri (Environmental Monitoring and Assessment, 2023)

Nutritional management of type 2 diabetes in subjects with obesity: an international guideline for clinical practice - Luigi Barrea; Claudia Vetrani; Massimiliano Caprio; Marwan El Ghoch; Evelyn Frias-Toral; Rucha J. Mehta; Verna Mendez; Eleonora Moriconi; Stavroula A. Paschou; Agnieszka Pazderska; Silvia Savastano; Annamaria Colao; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Substrate profiling of the Arabidopsis Ca2+-dependent protein kinase AtCPK4 and its Ricinus communis ortholog RcCDPK1 - Ryan Kilburn; Eric T. Fedosejevs; Devang Mehta; Faranak Soleimani; Mina Ghahremani; Jacqueline Monaghan; Jay J. Thelen; R. Glen Uhrig; Wayne A. Snedden; William C. Plaxton (Plant Science, 2023)

Individual blood concentrations of persistent organic pollutants and chemical elements, and COVID-19: A prospective cohort study in Barcelona - Miquel Porta; José Pumarega; Magda Gasull; Ruth Aguilar; Luis A. Henríquez-Hernández; Xavier Basagaña; Manuel Zumbado; Judit Villar-García; Cristina Rius; Sneha Mehta; Marta Vidal; Alfons Jimenez; et al. (Environmental Research, 2023)

The effect of ketamine and D-cycloserine on the high frequency resting EEG spectrum in humans - J. F. Nottage; A. Gabay; K. De Meyer; K. F. Herrik; J. F. Bastlund; S. R. Christensen; S. Gijsen; M. A. Mehta (Psychopharmacology, 2023)
Rationale Preclinical studies indicate that high-frequency oscillations, above 100 Hz (HFO:100–170 Hz), are a potential translatable biomarker for pharmacological studies, with the rapid acting antidepressant ketamine increasing both gamma (40–100 Hz) and HFO. Objectives To assess the effect of the uncompetitive NMDA antagonist ketamine, and of D-cycloserine (DCS), which acts at the glycine site on NMDA receptors on HFO in humans. Methods We carried out a partially double-blind, 4-way crossover study in 24 healthy male volunteers. Each participant received an oral tablet and an intravenous infusion on each of four study days. The oral treatment was either DCS (250 mg or 1000 mg) or placebo. The infusion contained 0.5 mg/kg ketamine or saline placebo. The four study conditions were therefore placebo-placebo, 250 mg DCS-placebo, 1000 mg DCS-placebo, or placebo-ketamine. Results Compared with placebo, frontal midline HFO magnitude was increased by ketamine ( p = 0.00014) and 1000 mg DCS ( p = 0.013). Frontal gamma magnitude was also increased by both these treatments. However, at a midline parietal location, only HFO were increased by DCS, and not gamma, whilst ketamine increased both gamma and HFO at this location. Ketamine induced psychomimetic effects, as measured by the PSI scale, whereas DCS did not increase the total PSI score. The perceptual distortion subscale scores correlated with the posterior low gamma to frontal high beta ratio. Conclusions Our results suggest that, at high doses, a partial NMDA agonist (DCS) has similar effects on fast neural oscillations as an NMDA antagonist (ketamine). As HFO were induced without psychomimetic effects, they may prove a useful drug development target.

Correction: Nanotechnology-Assisted Metered-Dose Inhalers (MDIs) for High-Performance Pulmonary Drug Delivery Applications - Raj Kumar; Piyush Mehta; Konathala Ravi Shankar; Manju A. K. Rajora; Yogendra Kumar Mishra; Ebrahim Mostafavi; Ajeet Kaushik (Pharmaceutical Research, 2022)

Nanotechnology-Assisted Metered-Dose Inhalers (MDIs) for High-Performance Pulmonary Drug Delivery Applications - Raj Kumar; Piyush Mehta; Konathala Ravi Shankar; Manju A. K. Rajora; Yogendra Kumar Mishra; Ebrahim Mostafavi; Ajeet Kaushik (Pharmaceutical Research, 2022)

Improving the ACS Triage—Using High Sensitivity TroponinI and Copeptin for Early ‘Rule-Out’ of AMI - M. Kankra; A. Mehta; J. P. S. Sawhney; S. Solanki; S. Bhargava; A. Ahirwar; A. Manocha; P. Singla; A. Sharma; M. Sharma (Indian Journal of Clinical Biochemistry, 2022)

Nutritional guidelines for the management of insulin resistance - Giovanna Muscogiuri; Luigi Barrea; Massimiliano Caprio; Florencia Ceriani; Alberto O. Chavez; Marwan El Ghoch; Evelyn Frias-Toral; Rucha J Mehta; Verna Mendez; Stavroula A. Paschou; Agnieszka Pazderska; Silvia Savastano; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Betamethasone Dipropionate Nanocrystals: Investigation, Feasibility and In Vitro Evaluation - Viral Patel; Tejal A. Mehta (AAPS PharmSciTech, 2022)

Differential contributions of serotonergic and dopaminergic functional connectivity to the phenomenology of LSD - Timothy Lawn; Ottavia Dipasquale; Alexandros Vamvakas; Ioannis Tsougos; Mitul A. Mehta; Matthew A. Howard (Psychopharmacology, 2022)
Rationale LSD is the prototypical psychedelic. Despite a clear central role of the 5HT 2a receptor in its mechanism of action, the contributions of additional receptors for which it shows affinity and agonist activity remain unclear. Objectives We employed receptor-enriched analysis of functional connectivity by targets (REACT) to explore differences in functional connectivity (FC) associated with the distributions of the primary targets of LSD—the 5HT 1a , 5HT 1b , 5HT 2a , D1 and D2 receptors. Methods We performed secondary analyses of an openly available dataset ( N = 15) to estimate the LSD-induced alterations in receptor-enriched FC maps associated with these systems. Principal component analysis (PCA) was employed as a dimension reduction strategy for subjective experiences associated with LSD captured by the Altered States of Consciousness (ASC) questionnaire. Correlations between these principal components as well as VAS ratings of subjective effects with receptor-enriched FC were explored. Results Compared to placebo, LSD produced differences in FC when the analysis was enriched with each of the primary serotonergic and dopaminergic receptors. Altered receptor-enriched FC showed relationships with the subjective effects of LSD on conscious experience, with serotonergic and dopaminergic systems being predominantly associated with perceptual effects and perceived selfhood as well as cognition respectively. These relationships were dissociable, with different receptors showing the same relationships within, but not between, the serotonergic and dopaminergic systems. Conclusions These exploratory findings provide new insights into the pharmacology of LSD and highlight the need for additional investigation of non-5HT 2a -mediated mechanisms.

Education Competencies for Integrative Oncology—Results of a Systematic Review and an International and Interprofessional Consensus Procedure - Claudia M. Witt; Lynda G. Balneaves; Linda E. Carlson; Misha Cohen; Gary Deng; Judith M. Fouladbakhsh; Anita Y. Kinney; Ashwin Mehta; Josh Mailman; Laura Pole; Alizé A. Rogge; Carole O’Toole; et al. (Journal of Cancer Education, 2022)
Integrative oncology is a burgeoning field and typically provided by a multiprofessional team. To ensure cancer patients receive effective, appropriate, and safe care, health professionals providing integrative cancer care should have a certain set of competencies. The aim of this project was to define core competencies for different health professions involved in integrative oncology. The project consisted of two phases. A systematic literature review on published competencies was performed, and the results informed an international and interprofessional consensus procedure. The second phase consisted of three rounds of consensus procedure and included 28 experts representing 7 different professions (medical doctors, psychologists, nurses, naturopathic doctors, traditional Chinese medicine practitioners, yoga practitioners, patient navigators) as well as patient advocates, public health experts, and members of the Society for Integrative Oncology. A total of 40 integrative medicine competencies were identified in the literature review. These were further complemented by 18 core oncology competencies. The final round of the consensus procedure yielded 37 core competencies in the following categories: knowledge ( n = 11), skills ( n = 17), and abilities ( n = 9). There was an agreement that these competencies are relevant for all participating professions. The integrative oncology core competencies combine both fundamental oncology knowledge and integrative medicine competencies that are necessary to provide effective and safe integrative oncology care for cancer patients. They can be used as a starting point for developing profession-specific learning objectives and to establish integrative oncology education and training programs to meet the needs of cancer patients and health professionals.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Hydrogen production, storage, utilisation and environmental impacts: a review - Ahmed I. Osman; Neha Mehta; Ahmed M. Elgarahy; Mahmoud Hefny; Amer Al-Hinai; Ala’a H. Al-Muhtaseb; David W. Rooney (Environmental Chemistry Letters, 2022)

Molecular Insights to the Wnt Signaling During Alzheimer’s Disorder: a Potential Target for Therapeutic Interventions - Priyanka Nagu; Vivek Sharma; Tapan Behl; Amjad Khan A. Pathan; Vineet Mehta (Journal of Molecular Neuroscience, 2022)

Higher buccal mitochondrial DNA and mitochondrial common deletion number are associated with markers of neurodegeneration and inflammation in cerebrospinal fluid - Dipesh Solanky; Jerel A. Fields; Jennifer E. Iudicello; Ronald J. Ellis; Donald Franklin; David B. Clifford; Benjamin B. Gelman; Christina M. Marra; Susan Morgello; Leah H. Rubin; Igor Grant; Robert K. Heaton; et al. (Journal of NeuroVirology, 2022)

Mapping the effects of atomoxetine during response inhibition across cortical territories and the locus coeruleus - Rong Ye; Ndabezinhle Mazibuko; Jens Teichert; Ralf Regenthal; Angie A. Kehagia; Mitul A. Mehta (Psychopharmacology, 2022)

Hydrogen production, storage, utilisation and environmental impacts: a review - Ahmed I. Osman; Neha Mehta; Ahmed M. Elgarahy; Mahmoud Hefny; Amer Al-Hinai; Ala’a H. Al-Muhtaseb; David W. Rooney (Environmental Chemistry Letters, 2022)
Dihydrogen (H 2 ), commonly named ‘hydrogen’, is increasingly recognised as a clean and reliable energy vector for decarbonisation and defossilisation by various sectors. The global hydrogen demand is projected to increase from 70 million tonnes in 2019 to 120 million tonnes by 2024. Hydrogen development should also meet the seventh goal of ‘affordable and clean energy’ of the United Nations. Here we review hydrogen production and life cycle analysis, hydrogen geological storage and hydrogen utilisation. Hydrogen is produced by water electrolysis, steam methane reforming, methane pyrolysis and coal gasification. We compare the environmental impact of hydrogen production routes by life cycle analysis. Hydrogen is used in power systems, transportation, hydrocarbon and ammonia production, and metallugical industries. Overall, combining electrolysis-generated hydrogen with hydrogen storage in underground porous media such as geological reservoirs and salt caverns is well suited for shifting excess off-peak energy to meet dispatchable on-peak demand.

Conversion of biomass to biofuels and life cycle assessment: a review - Ahmed I. Osman; Neha Mehta; Ahmed M. Elgarahy; Amer Al-Hinai; Ala’a H. Al-Muhtaseb; David W. Rooney (Environmental Chemistry Letters, 2021)
The global energy demand is projected to rise by almost 28% by 2040 compared to current levels. Biomass is a promising energy source for producing either solid or liquid fuels. Biofuels are alternatives to fossil fuels to reduce anthropogenic greenhouse gas emissions. Nonetheless, policy decisions for biofuels should be based on evidence that biofuels are produced in a sustainable manner. To this end, life cycle assessment (LCA) provides information on environmental impacts associated with biofuel production chains. Here, we review advances in biomass conversion to biofuels and their environmental impact by life cycle assessment. Processes are gasification, combustion, pyrolysis, enzymatic hydrolysis routes and fermentation. Thermochemical processes are classified into low temperature, below 300 °C, and high temperature, higher than 300 °C, i.e. gasification, combustion and pyrolysis. Pyrolysis is promising because it operates at a relatively lower temperature of up to 500 °C, compared to gasification, which operates at 800–1300 °C. We focus on 1) the drawbacks and advantages of the thermochemical and biochemical conversion routes of biomass into various fuels and the possibility of integrating these routes for better process efficiency; 2) methodological approaches and key findings from 40 LCA studies on biomass to biofuel conversion pathways published from 2019 to 2021; and 3) bibliometric trends and knowledge gaps in biomass conversion into biofuels using thermochemical and biochemical routes. The integration of hydrothermal and biochemical routes is promising for the circular economy.

Biomass, carbon stocks estimation and predictive modeling in mango based land uses on degraded lands in Indian Sub-Himalayas - Avinash Chandra Rathore; Harsh Mehta; Sadikul Islam; P. L. Saroj; N. K. Sharma; J. Jayaprakash; A. K. Gupta; R. K. Dubey; B. N. Ghosh; Ram Prasad; Dinesh Kumar; A. Raizada (Agroforestry Systems, 2021)

Recessive ciliopathy mutations in primary endocardial fibroelastosis: a rare neonatal cardiomyopathy in a case of Alstrom syndrome - Yan Zhao; Lee-kai Wang; Ascia Eskin; Xuedong Kang; Viviana M. Fajardo; Zubin Mehta; Stacy Pineles; Ryan J. Schmidt; Aaron Nagiel; Gary Satou; Meena Garg; Myke Federman; et al. (Journal of Molecular Medicine, 2021)
Among neonatal cardiomyopathies, primary endocardial fibroelastosis (pEFE) remains a mysterious disease of the endomyocardium that is poorly genetically characterized, affecting 1/5000 live births and accounting for 25% of the entire pediatric dilated cardiomyopathy (DCM) with a devastating course and grave prognosis. To investigate the potential genetic contribution to pEFE, we performed integrative genomic analysis, using whole exome sequencing (WES) and RNA-seq in a female infant with confirmed pathological diagnosis of pEFE. Within regions of homozygosity in the proband genome, WES analysis revealed novel parent-transmitted homozygous mutations affecting three genes with known roles in cilia assembly or function. Among them, a novel homozygous variant [c.1943delA] of uncertain significance in ALMS1 was prioritized for functional genomic and mechanistic analysis. Loss of function mutations of ALMS1 have been implicated in Alstrom syndrome (AS) [OMIM 203800], a rare recessive ciliopathy that has been associated with cardiomyopathy. The variant of interest results in a frameshift introducing a premature stop codon. RNA-seq of the proband’s dermal fibroblasts confirmed the impact of the novel ALMS1 variant on RNA-seq reads and revealed dysregulated cellular signaling and function, including the induction of epithelial mesenchymal transition (EMT) and activation of TGFβ signaling. ALMS1 loss enhanced cellular migration in patient fibroblasts as well as neonatal cardiac fibroblasts, while ALMS1-depleted cardiomyocytes exhibited enhanced proliferation activity. Herein, we present the unique pathological features of pEFE compared to DCM and utilize integrated genomic analysis to elucidate the molecular impact of a novel mutation in ALMS1 gene in an AS case. Our report provides insights into pEFE etiology and suggests, for the first time to our knowledge, ciliopathy as a potential underlying mechanism for this poorly understood and incurable form of neonatal cardiomyopathy. Key message Primary endocardial fibroelastosis (pEFE) is a rare form of neonatal cardiomyopathy that occurs in 1/5000 live births with significant consequences but unknown etiology. Integrated genomics analysis (whole exome sequencing and RNA sequencing) elucidates novel genetic contribution to pEFE etiology. In this case, the cardiac manifestation in Alstrom syndrome is pEFE. To our knowledge, this report provides the first evidence linking ciliopathy to pEFE etiology. Infants with pEFE should be examined for syndromic features of Alstrom syndrome. Our findings lead to a better understanding of the molecular mechanisms of pEFE, paving the way to potential diagnostic and therapeutic applications.

Development and Optimization of Asenapine Sublingual Film Using QbD Approach - Rahil Dalal; Jigar Shah; Bapi Gorain; Hira Choudhury; Shery Jacob; Tejal A. Mehta; Hiral Shah; Anroop B. Nair (AAPS PharmSciTech, 2021)

Eco-evolutionary dynamics of autotomy - Rohan S. Mehta; Julie A. Kraus (Theoretical Ecology, 2021)

Bioaccessibility of metals in soils surrounding two dismissed mining sites in Northern Italy - E. Padoan; C. Romè; N. Mehta; G. A. Dino; D. A. De Luca; F. Ajmone-Marsan (International Journal of Environmental Science and Technology, 2021)
Mining activities are one of the main contributors to metals contamination of soils, most often due to the inappropriate management of the mining residues. In Italy, hundreds of small mining sites are scattered around the mountainous areas, near small villages with fragile environments. Here, wastes and residues may have polluted the surrounding soils and become a threat to living organisms. We investigated two dismissed sites in Northern Italy with extractive wastes in unmanaged areas close to villages using bioaccessibility and size fractionation methods, focussing on particles that can potentially be eroded and/or ingested (< 10 µm and < 200 µm). In the Campello Monti site, Co, Cu and Ni showed high values in soils near the landfills, with the highest concentrations in the < 10 µm particles around the landfills and along the valley bottom. Lead and Ni were the most bioaccessible metals. In the Plassa site, Cd and Zn were the most important contaminants, with an average content of 118 and 34,000 mg/kg. They originated from mining wastes scattered through the slope and had a particularly high bioaccessible fractions, close to the 100% for Zn and above 80% for Cd in the fine particles. The study of the fine, more reactive and mobile particles offered a close insight into the lability of contaminants, as in both sites, a dispersion of metal contaminants through very fine particles in surrounding and downhill areas was observed, resulting in an increased risk to all living organism and for the environment.

Challenges in CNS drug development and the role of imaging - Oliver D. Howes; Mitul A. Mehta (Psychopharmacology, 2021)

An experimental medicine study of the phosphodiesterase-4 inhibitor, roflumilast, on working memory-related brain activity and episodic memory in schizophrenia patients - James Gilleen; Yakub Farah; Cate Davison; Sarah Kerins; Lorena Valdearenas; Tolga Uz; Gez Lahu; Max Tsai; Frank Ogrinc; Avi Reichenberg; Steve C. Williams; Mitul A. Mehta; et al. (Psychopharmacology, 2021)
Rationale Schizophrenia is associated with impairments in cognitive functioning yet there are no approved drugs to treat these deficits. Objectives Based on animal models, we investigated the potential for roflumilast, a selective inhibitor of phosphodiesterase type 4 (PDE4), to improve cognition, which may act by increasing intracellular cyclic adenosine monophosphate in brain regions underlying cognitive deficits in schizophrenia. Methods This study consisted of a randomised, double-blind, placebo-controlled, crossover design involving 15 schizophrenia patients. In 3 treatment periods, patients were given 8 days of placebo or one of the two doses of roflumilast (100 and 250 μg daily) with 14 days of washout between treatments. The primary endpoints were dorsolateral prefrontal cortex (DLPFC) activation during a visuospatial working memory task measured with fMRI on dosing day 8 and verbal memory and working memory performance change from baseline to day 8. Least square mean change scores were calculated for behavioural outcomes; fMRI data were analysed in SPM12 with bilateral DLPFC as regions of interest. Results Verbal memory was significantly improved under 250 μg roflumilast (effect size (ES) = 0.77) compared to placebo. fMRI analyses revealed that increasing dose of roflumilast was associated with reduction of bilateral DLPFC activation during working memory compared to placebo, although this was not statistically significant (ES = 0.31 for the higher dose). Working memory was not improved (ES = 0.03). Conclusions Results support the mechanistic validation of potential novel strategies for improving cognitive dysfunction in schizophrenia and suggest that PDE4 inhibition may be beneficial for cognitive dysfunction in schizophrenia. Trial registration NCT02079844 .

MSC exosome-mediated cardioprotection in ischemic mouse heart comparative proteomics of infarct and peri-infarct areas - Rajshekhar A. Kore; Xianwei Wang; Zufeng Ding; Robert J. Griffin; Alan J. Tackett; Jawahar L. Mehta (Molecular and Cellular Biochemistry, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Emerging Nanomedicines for the Treatment of Atopic Dermatitis - Khushali Parekh; Tejal A Mehta; Namdev Dhas; Pavan Kumar; Amirali Popat (AAPS PharmSciTech, 2021)

Antimicrobial peptide polymers: no escape to ESKAPE pathogens—a review - Songhita Mukhopadhyay; A. S. Bharath Prasad; Chetan H. Mehta; Usha Y. Nayak (World Journal of Microbiology and Biotechnology, 2020)
Antimicrobial resistance (AMR) is one of the significant clinical challenges and also an emerging area of concern arising from nosocomial infections of ESKAPE pathogens, which has been on the rise in both the developed and developing countries alike . These pathogens/superbugs can undergo rapid mutagenesis, which helps them to generate resistance against antimicrobials in addition to the patient’s non-adherence to the antibiotic regimen. Sticking to the idea of a ‘one-size-fits-all’ approach has led to the inappropriate administration of antibiotics resulting in augmentation of antimicrobial resistance. Antimicrobial peptides (AMPs) are the natural host defense peptides that have gained attention in the field of AMR, and recently, synthetic AMPs are well studied to overcome the drawbacks of natural counterparts. This review deals with the novel techniques utilizing the bacteriolytic activity of natural AMPs. The effective localization of these peptides onto the negatively charged bacterial surface by using nanocarriers and structurally nanoengineered antimicrobial peptide polymers (SNAPPs) owing to its smaller size and better antimicrobial activity is also described here. Graphic abstract

Cellular signalling pathways mediating the pathogenesis of chronic inflammatory respiratory diseases: an update - Meenu Mehta; Daljeet S. Dhanjal; Keshav R. Paudel; Bhupender Singh; Gaurav Gupta; S. Rajeshkumar; Lakshmi Thangavelu; Murtaza M. Tambuwala; Hamid A. Bakshi; Dinesh K. Chellappan; Parijat Pandey; Harish Dureja; et al. (Inflammopharmacology, 2020)

Diversity of hepatitis C virus infection among HIV-infected people who inject drugs in India - S. S. Solomon; D. Boon; S. Saravanan; A. K. Srikrishnan; C. K. Vasudevan; P. Balakrishnan; D. Persaud; S. C. Ray; S. Mehta; S. H. Mehta (VirusDisease, 2019)

Impact of Process Parameters on Particle Size Involved in Media Milling Technique Used for Preparing Clotrimazole Nanocrystals for the Management of Cutaneous Candidiasis - Viral Patel; Om Prakash Sharma; Tejal A. Mehta (AAPS PharmSciTech, 2019)

Effect of Delay in Deskinning and Lipid Oxidation on Pink Discoloration of Squid During Ice Storage - M. A. Muhasinath; N. K. Mehta; R. Prasadnaik; M. K. Chouksey; B. B. Nayak (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Adaptation of Desulfovibrio alaskensis G20 to perchlorate, a specific inhibitor of sulfate reduction - Misha G. Mehta‐Kolte; Magdalena K. Stoeva; Anchal Mehra; Steven A. Redford; Matthew D. Youngblut; Grant Zane; Patrick Grégoire; Hans K. Carlson; Judy Wall; John D. Coates (Environmental Microbiology, 2019)
Summary Hydrogen sulfide produced by sulfate‐reducing microorganisms (SRM) poses significant health and economic risks, particularly during oil recovery. Previous studies identified perchlorate as a specific inhibitor of SRM. However, constant inhibitor addition to natural systems results in new selective pressures. Consequently, we investigated the ability of Desulfovibrio alaskensis G20 to evolve perchlorate resistance. Serial transfers in increasing concentrations of perchlorate led to robust growth in the presence of 100 mM inhibitor. Isolated adapted strains demonstrated a threefold increase in perchlorate resistance compared to the wild‐type ancestor. Whole genome sequencing revealed a single base substitution in Dde_2265, the sulfate adenylyltransferase ( sat ). We purified and biochemically characterized the Sat from both wild‐type and adapted strains, and showed that the adapted Sat was approximately threefold more resistant to perchlorate inhibition, mirroring whole cell results. The ability of this mutation to confer resistance across other inhibitors of sulfidogenesis was also assayed. The generalizability of this mutation was confirmed in multiple evolving G20 cultures and in another SRM, D. vulgaris Hildenborough. This work demonstrates that a single nucleotide polymorphism in Sat can have a significant impact on developing perchlorate resistance and emphasizes the value of adaptive laboratory evolution for understanding microbial responses to environmental perturbations.

Surface Ocean Dispersion Observations From the Ship-Tethered Aerostat Remote Sensing System - Daniel F. Carlson; Tamay Özgökmen; Guillaume Novelli; Cedric Guigand; Henry Chang; Baylor Fox-Kemper; Jean Mensa; Sanchit Mehta; Erick Fredj; Helga Huntley; A. D. Kirwan; Maristella Berta; et al. (Frontiers in Marine Science, 2018)

Effects of ketamine on brain function during response inhibition - M. Steffens; C. Neumann; A.-M. Kasparbauer; B. Becker; B. Weber; M. A. Mehta; R. Hurlemann; U. Ettinger (Psychopharmacology, 2018)

A mouse model of the Δ133p53 isoform: roles in cancer progression and inflammation - Marina Kazantseva; Sunali Mehta; Ramona A. Eiholzer; Noelyn Hung; Anna Wiles; Tania L. Slatter; Antony W. Braithwaite (Mammalian Genome, 2018)

Eat whole and less often: ontogenetic shift reveals size specialization on kelp bass by the California moray eel, Gymnothorax mordax - Benjamin A. Higgins; Chris J. Law; Rita S. Mehta (Oecologia, 2018)

Effect of geojute technique on density, diversity and carbon stock of plant species in landslide site of North West Himalaya - Harsh Mehta; Raj Kumar; M. Ayub Dar; G. P. Juyal; Sridhar Patra; Sneha Dobhal; A. C. Rathore; Rajesh Kaushal; P. K. Mishra (Journal of Mountain Science, 2018)

Group II metabotropic glutamate receptor agonist prodrugs LY2979165 and LY2140023 attenuate the functional imaging response to ketamine in healthy subjects - Mitul A. Mehta; Anne Schmechtig; Vasileia Kotoula; Juliet McColm; Kimberley Jackson; Claire Brittain; Sitra Tauscher-Wisniewski; Bruce J. Kinon; Paul D. Morrison; Thomas Pollak; Timothy Mant; Steven C. R. Williams; et al. (Psychopharmacology, 2018)

Target Specific Anticoagulant Peptides: A Review - Azeemullah A. Syed; Alka Mehta (International Journal of Peptide Research and Therapeutics, 2018)

Predictive models for biomass and carbon stock estimation in Psidium guajava on bouldery riverbed lands in North-Western Himalayas, India - A. C. Rathore; Abhishek Kumar; J. M. S. Tomar; J. Jayaprakash; H. Mehta; R. Kaushal; N. M. Alam; A. K. Gupta; A. Raizada; O. P. Chaturvedi (Agroforestry Systems, 2018)

Distribution and habitat associations of the California moray (Gymnothorax mordax) within Two Harbors, Santa Catalina Island, California - B. A. Higgins; R. S. Mehta (Environmental Biology of Fishes, 2018)

SCMR: A More Pertinent Trait than SLA in Peanut Genotypes Under Transient Water Deficit Stress During Summer - K. A. Kalariya; A. L. Singh; K. Chakraborty; B. C. Ajay; P. V. Zala; C. B. Patel; R. N. Nakar; Nisha Goswami; Deepti Mehta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

El N iño episodes coincide with C alifornia moray G ymnothorax mordax settlement around S anta C atalina I sland, C alifornia - B. A. Higgins; D. Pearson; R. S. Mehta (Journal of Fish Biology, 2017)
The hypothesis that El Niño events influence the settlement patterns of the California moray Gymnothorax mordax is tested. The pelagic larval duration ( PLD ) of larval G. mordax is unknown, but studies on leptocephalus of related species suggest that larvae are long‐lived, up to 2 years. Gymnothorax mordax , an elusive predatory species and the only muraenid off the coast of California, is considered abundant in the waters around Catalina Island. Thirty‐three individuals were collected from Two Harbors, Catalina Island, and otoliths were taken to provide estimates of their age. Settlement year for each individual was backcalculated using estimated age from otolith measurements. These ages were then cross referenced with the Oceanic Niño Index ( ONI ) developed by the National Oceanographic and Atmospheric Administration ( NOAA ) to correlate estimated age of settlement with known El Niño years. Of the 33 individuals collected, 30 settled at Catalina Island during El Niño years. The oldest individual in the data‐set was 22 years old, placing G. mordax as one of the longer‐lived predatory fishes in the system. The present study represents the first account of wild G. mordax ages and suggests that El Niño events have an important role in driving the settlement of recruits towards the northern edge of their range.

Investigation into the Effect of Ethylcellulose Viscosity Variation on the Drug Release of Metoprolol Tartrate and Acetaminophen Extended Release Multiparticulates—Part I - R. Mehta; J. Teckoe; C. Schoener; S. Workentine; D. Ferrizzi; A. Rajabi-Siahboomi (AAPS PharmSciTech, 2016)

Association between IL28B rs12979860 single nucleotide polymorphism and the frequency of colonic Treg in chronically HCV-infected patients - Minesh Mehta; Helal F. Hetta; Enass A. Abdel-hameed; Susan D. Rouster; MdMonir Hossain; Mohamed A. Mekky; Nasr K. Khalil; Wegdan A. Mohamed; Mohamed A. El-Feky; Shabaan H. Ahmed; Enas A. Daef; Mohamed A. El-Mokhtar; et al. (Archives of Virology, 2016)

Regeneration complexities of Pinus gerardiana in dry temperate forests of Indian Himalaya - Raj Kumar; G. S. Shamet; Harsh Mehta; N. M. Alam; Rajesh Kaushal; O. P. Chaturvedi; Navneet Sharma; B. A. Khaki; Dinesh Gupta (Environmental Science and Pollution Research, 2016)

Monitoring land use change and its drivers in Delhi, India using multi-temporal satellite data - Madhavi Jain; Dorje Dawa; Rajender Mehta; A. P. Dimri; M. K. Pandit (Modeling Earth Systems and Environment, 2016)

A Synergistic Role of Myeloperoxidase and High Sensitivity Troponin T in the Early Diagnosis of Acute Coronary Syndrome - Mihir D. Mehta; Simbita A. Marwah; S. Ghosh; Hitesh Shah; Amit Trivedi; N. Haridas (Indian Journal of Clinical Biochemistry, 2016)

Weighing the Evidence of Common Beliefs in Obesity Research - Krista Casazza; Andrew Brown; Arne Astrup; Fredrik Bertz; Charles Baum; Michelle Bohan Brown; John Dawson; Nefertiti Durant; Gareth Dutton; David A. Fields; Kevin R. Fontaine; Steven Heymsfield; et al. (Critical Reviews in Food Science and Nutrition, 2015)

Phenomenologically distinct psychotomimetic effects of ketamine are associated with cerebral blood flow changes in functionally relevant cerebral foci: a continuous arterial spin labelling study - T. A. Pollak; S. De Simoni; B. Barimani; F. O. Zelaya; J. M. Stone; M. A. Mehta (Psychopharmacology, 2015)

Modulatory effects of ketamine, risperidone and lamotrigine on resting brain perfusion in healthy human subjects - Sergey Shcherbinin; Orla Doyle; Fernando O. Zelaya; Sara de Simoni; Mitul A. Mehta; Adam J. Schwarz (Psychopharmacology, 2015)

The role of machine learning in neuroimaging for drug discovery and development - Orla M. Doyle; Mitul A. Mehta; Michael J. Brammer (Psychopharmacology, 2015)

Ketamine induces a robust whole-brain connectivity pattern that can be differentially modulated by drugs of different mechanism and clinical profile - R. Joules; O. M. Doyle; A. J. Schwarz; O. G. O’Daly; M. Brammer; S. C. Williams; M. A. Mehta (Psychopharmacology, 2015)

Exogenous interferon prolongs survival of rabies infected mice - S. Mehta; S. Roy; S. Mukherjee; N. Yadav; N. Patel; A. Chowdhary (VirusDisease, 2015)

Further human evidence for striatal dopamine release induced by administration of ∆9-tetrahydrocannabinol (THC): selectivity to limbic striatum - Matthijs G. Bossong; Mitul A. Mehta; Bart N. M. van Berckel; Oliver D. Howes; René S. Kahn; Paul R. A. Stokes (Psychopharmacology, 2015)

Photosynthetic characteristics of peanut genotypes under excess and deficit irrigation during summer - Kuldeepsingh A. Kalariya; Amrit Lal Singh; Nisha Goswami; Deepti Mehta; Mahesh Kumar Mahatma; B. C. Ajay; Koushik Chakraborty; P. V. Zala; Vidya Chaudhary; C. B. Patel (Physiology and Molecular Biology of Plants, 2015)

Differences in genetic variation in antigen-processing machinery components and association with cervical carcinoma risk in two Indonesian populations - Akash M. Mehta; Vivian M. Spaans; Nyoman Bayu Mahendra; Elisabeth M. Osse; Jessica N. I. Vet; Gatot Purwoto; I. G. D. Surya; Santoso Cornian; Alexander A. Peters; Gert J. Fleuren; Ekaterina S. Jordanova (Immunogenetics, 2015)

Drug Access to the Central Nervous System in Alzheimer’s Disease: Preclinical and Clinical Insights - Dharmini C. Mehta; Jennifer L. Short; Sarah N. Hilmer; Joseph A. Nicolazzo (Pharmaceutical Research, 2015)

Hydroxy propyl β-cyclodextrin complexation of promethazine hydrochloride for the formulation of fast dissolving sublingual film: in vitro and in vivo evaluation - Jigar N. Shah; Kashyap N. Shah; Tejal A. Mehta (Journal of Pharmaceutical Investigation, 2015)

On-farm status of rice (Oryza sativa L.) genetic resources in Garhwal Himalaya of Uttarakhand, India - P. S. Mehta; S. N. Ojha; K. S. Negi; S. K. Verma; A. Rayal; R. K. Tyagi (Genetic Resources and Crop Evolution, 2014)

Predictive models for biomass and carbon stocks estimation in Grewia optiva on degraded lands in western Himalaya - Archana Verma; R. Kaushal; N. M. Alam; H. Mehta; O. P. Chaturvedi; D. Mandal; J. M. S. Tomar; A. C. Rathore; Charan Singh (Agroforestry Systems, 2014)

Discrimination between Babul plantations and Mustard crop using Polarimetric C- and L- band data - R. L. Mehta; N. Parihar; A. Sinha; B. P. Shastri; M. Chakraborty (Journal of the Indian Society of Remote Sensing, 2014)

An efficient synthesis, characterization, and antimicrobial screening of tetrahydropyrimidine derivatives - Dinesh R. Godhani; Purvesh B. Dobariya; Anand A. Jogel; Anil M. Sanghani; Jignasu P. Mehta (Medicinal Chemistry Research, 2014)

Altered Brain Uptake of Therapeutics in a Triple Transgenic Mouse Model of Alzheimer’s Disease - Dharmini C. Mehta; Jennifer L. Short; Joseph A. Nicolazzo (Pharmaceutical Research, 2013)

The role of P-glycoprotein in CNS antihistamine effects - Silke Conen; Eef L. Theunissen; Annemiek Vermeeren; Peter van Ruitenbeek; Peter Stiers; Mitul A. Mehta; Stefan W. Toennes; Johannes G. Ramaekers (Psychopharmacology, 2013)

Pharmacokinetics of colistin in critically ill patients with multidrug-resistant Gram-negative bacilli infection - Niteen D. Karnik; Kannan Sridharan; Sonali P. Jadhav; Prashant P. Kadam; Raghu K. Naidu; Rahul D. Namjoshi; Vishal Gupta; Mangesh S. Gore; Pallavi V. Surase; Preeti R. Mehta; Jaideep A. Gogtay; Urmila M. Thatte; et al. (European Journal of Clinical Pharmacology, 2013)

Improvement of dissolution rate of tacrolimus by solid dispersion technique - Pranav V. Patel; Shital S. Panchal; Tejal A. Mehta (Journal of Pharmaceutical Investigation, 2013)

Systematic review and meta-analysis of epidemiological time-series studies on outdoor air pollution and health in Asia - R. W. Atkinson; A. Cohen; S. Mehta; H. R. Anderson (Air Quality, Atmosphere & Health, 2012)

Design, synthesis, characterization, and in vitro antimicrobial action of novel trisubstituted s-triazines - Paresh K. Patel; Rahul V. Patel; Dharmesh H. Mahajan; Parimal A. Parikh; Girish N. Mehta; Kishor H. Chikhalia (Medicinal Chemistry Research, 2012)

Picture-naming in patients with left frontal lobe tumor – a functional neuroimaging study - Anya Chakraborty; T. A. Sumathi; Veer Singh Mehta; Nandini Chatterjee Singh (Brain Imaging and Behavior, 2012)

Modifying agricultural water management to adapt to climate change in California’s central valley - Brian A. Joyce; Vishal K. Mehta; David R. Purkey; Larry L. Dale; Michael Hanemann (Climatic Change, 2011)

Understanding protein kinase CK2 mis-regulation upon F508del CFTR expression - Andrea Venerando; Mario A. Pagano; Kendra Tosoni; Flavio Meggio; Diane Cassidy; Michelle Stobbart; Lorenzo A. Pinna; Anil Mehta (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

The cellulose contents of Indian seaweeds - A. K. Siddhanta; Mahesh U. Chhatbar; Gaurav K. Mehta; Naresh D. Sanandiya; Sanjay Kumar; Mihir D. Oza; Kamalesh Prasad; Ramavatar Meena (Journal of Applied Phycology, 2011)

Identification of defence-related genes expressed in coffee and citrus during infection by Xylella fastidiosa - Marcelo F. Carazzolle; Fernanda R. Rabello; Natália F. Martins; Alessandra A. de Souza; Alexandre M. do Amaral; Juliana Freitas-Astua; Gonçalo A. G. Pereira; Marcos A. Machado; Angela Mehta (European Journal of Plant Pathology, 2011)

Preparation of galactans from Gracilaria debilis and Gracilaria salicornia (Gracilariales, Rhodophyta) of Indian waters - Gaurav K. Mehta; Ramavatar Meena; Kamalesh Prasad; M. Ganesan; A. K. Siddhanta (Journal of Applied Phycology, 2010)

Bacterial diversity in the rumen of Indian Surti buffalo (Bubalus bubalis), assessed by 16S rDNA analysis - P. R. Pandya; K. M. Singh; S. Parnerkar; A. K. Tripathi; H. H. Mehta; D. N. Rank; R. K. Kothari; C. G. Joshi (Journal of Applied Genetics, 2010)

Panel of synaptic protein ELISAs for evaluating neurological phenotype - Paul E. Gottschall; Joanne M. Ajmo; Autumn K. Eakin; Matthew D. Howell; Hina Mehta; Lauren A. Bailey (Experimental Brain Research, 2010)

Responses of thoracic spinal interneurons to vestibular stimulation - D. M. Miller; D. A. Reighard; Amar S. Mehta; Ajeet S. Mehta; R. Kalash; B. J. Yates (Experimental Brain Research, 2009)

The pharmacokinetic profile of recombinant human erythropoietin is unchanged in patients undergoing cardiac surgery - Stuart A. McCluskey; Wing K. Cheung; Rita Katznelson; Humara Poonawala; Ludwik Fedorko; George Djaiani; Bobby Mehta; Keyvan Karkouti (European Journal of Clinical Pharmacology, 2009)

Molecular mapping of Cg1, a gene for resistance to anthracnose (Colletotrichum sublineolum) in sorghum - P. Ramasamy; M. A. Menz; P. J. Mehta; S. Katilé; L. A. Gutierrez-Rojas; R. R. Klein; P. E. Klein; L. K. Prom; J. A. Schlueter; W. L. Rooney; C. W. Magill (Euphytica, 2009)

Ga3+ as a mechanistic probe in Fe3+ transport: characterization of Ga3+ interaction with FbpA - Katherine D. Weaver; Jared J. Heymann; Arnav Mehta; Petra L. Roulhac; Damon S. Anderson; Andrew J. Nowalk; Pratima Adhikari; Timothy A. Mietzner; Michael C. Fitzgerald; Alvin L. Crumbliss (JBIC Journal of Biological Inorganic Chemistry, 2008)

Effect of telmisartan on cardiovascular complications associated with streptozotocin diabetic rats - Bhoomika R. Goyal; Pravin Mesariya; Ramesh K. Goyal; Anita A. Mehta (Molecular and Cellular Biochemistry, 2008)

A Numerical Model Simulating the Remediation of Hydrocarbon-Impacted Soils Using Low-Temperature Oxidation - M. Kashir; K. Zhang; G. Achari; R. G. Moore; S. A. Mehta; M. G. Ursenbach (Environmental Modeling & Assessment, 2008)

Dopamine D2 receptor occupancy levels of acute sulpiride challenges that produce working memory and learning impairments in healthy volunteers - Mitul A. Mehta; Andrew J. Montgomery; Yuri Kitamura; Paul M. Grasby (Psychopharmacology, 2008)

KILLER WHALES AND MARINE MAMMAL TRENDS IN THE NORTH PACIFIC—A RE‐EXAMINATION OF EVIDENCE FOR SEQUENTIAL MEGAFAUNA COLLAPSE AND THE PREY‐SWITCHING HYPOTHESIS - Paul R. Wade; Vladimir N. Burkanov; Marilyn E. Dahlheim; Nancy A. Friday; Lowell W. Fritz; Thomas R. Loughlin; Sally A. Mizroch; Marcia M. Muto; Dale W. Rice; Lance G. Barrett‐Lennard; Nancy A. Black; Alexander M. Burdin; et al. (Marine Mammal Science, 2007)
Springer et al . (2003) contend that sequential declines occurred in North Pacific populations of harbor and fur seals, Steller sea lions, and sea otters. They hypothesize that these were due to increased predation by killer whales, when industrial whaling's removal of large whales as a supposed primary food source precipitated a prey switch. Using a regional approach, we reexamined whale catch data, killer whale predation observations, and the current biomass and trends of potential prey, and found little support for the prey‐switching hypothesis. Large whale biomass in the Bering Sea did not decline as much as suggested by Springer et al ., and much of the reduction occurred 50–100 yr ago, well before the declines of pinnipeds and sea otters began; thus, the need to switch prey starting in the 1970s is doubtful. With the sole exception that the sea otter decline followed the decline of pinnipeds, the reported declines were not in fact sequential. Given this, it is unlikely that a sequential megafaunal collapse from whales to sea otters occurred. The spatial and temporal patterns of pinniped and sea otter population trends are more complex than Springer et al . suggest, and are often inconsistent with their hypothesis. Populations remained stable or increased in many areas, despite extensive historical whaling and high killer whale abundance. Furthermore, observed killer whale predation has largely involved pinnipeds and small cetaceans; there is little evidence that large whales were ever a major prey item in high latitudes. Small cetaceans (ignored by Springer et al .) were likely abundant throughout the period. Overall, we suggest that the Springer et al . hypothesis represents a misleading and simplistic view of events and trophic relationships within this complex marine ecosystem.

Ethics-in-oncology forums - Paulette Mehta; Micah Hester; A. Mazin Safar; Reed Thompson (Journal of Cancer Education, 2007)

A comparison of some population density sampling techniques for biodiversity, conservation, and environmental impact studies - Gerald J. Bakus; Gregory Nishiyama; Eduardo Hajdu; Hetal Mehta; Mahadi Mohammad; Ulisses dos S. Pinheiro; Stephen A. Sohn; Thaddeus K. Pham; Zulfigar bin Yasin; Tan Shau-Hwai; Abraham Karam; Erin Hanan (Biodiversity and Conservation, 2007)

Assessment of Ambient Air Quality in Urban Centres of Haryana (India) in Relation to Different Anthropogenic Activities and Health Risks - C. P. Kaushik; Khaiwal Ravindra; Krishan Yadav; Surender Mehta; A. K. Haritash (Environmental Monitoring and Assessment, 2006)

Microarray and genetic analysis of electron transfer to electrodes in Geobacter sulfurreducens - Dawn E. Holmes; Swades K. Chaudhuri; Kelly P. Nevin; Teena Mehta; Barbara A. Methé; Anna Liu; Joy E. Ward; Trevor L. Woodard; Jennifer Webster; Derek R. Lovley (Environmental Microbiology, 2006)
Summary Whole‐genome analysis of gene expression in Geobacter sulfurreducens revealed 474 genes with transcript levels that were significantly different during growth with an electrode as the sole electron acceptor versus growth on Fe(III) citrate. The greatest response was a more than 19‐fold increase in transcript levels for omcS , which encodes an outer‐membrane cytochrome previously shown to be required for Fe(III) oxide reduction. Quantitative reverse transcription polymerase chain reaction and Northern analyses confirmed the higher levels of omcS transcripts, which increased as power production increased. Deletion of omcS inhibited current production that was restored when omcS was expressed in trans. Transcript expression and genetic analysis suggested that OmcE, another outer‐membrane cytochrome, is also involved in electron transfer to electrodes. Surprisingly, genes for other proteins known to be important in Fe(III) reduction such as the outer‐membrane c ‐type cytochrome, OmcB, and the electrically conductive pilin ‘nanowires’ did not have higher transcript levels on electrodes, and deletion of the relevant genes did not inhibit power production. Changes in the transcriptome suggested that cells growing on electrodes were subjected to less oxidative stress than cells growing on Fe(III) citrate and that a number of genes annotated as encoding metal efflux proteins or proteins of unknown function may be important for growth on electrodes. These results demonstrate for the first time that it is possible to evaluate gene expression, and hence the metabolic state, of microorganisms growing on electrodes on a genome‐wide basis and suggest that OmcS, and to a lesser extent OmcE, are important in electron transfer to electrodes. This has important implications for the design of electrode materials and the genetic engineering of microorganisms to improve the function of microbial fuel cells.

Morphodynamic relationships for ebb and flood delta volumes at Florida’s tidal entrances - Mark A. Powell; Robert J. Thieke; Ashish J. Mehta (Ocean Dynamics, 2006)

Unified Approach for Multiple Sclerosis Lesion Segmentation on Brain MRI - Balasrinivasa Rao Sajja; Sushmita Datta; Renjie He; Meghana Mehta; Rakesh K. Gupta; Jerry S. Wolinsky; Ponnada A. Narayana (Annals of Biomedical Engineering, 2006)

Potentiation of cocaine-primed reinstatement of drug seeking in female rats during estrus - Tod E. Kippin; Rita A. Fuchs; Ritu H. Mehta; Jordan M. Case; Macon P. Parker; Heather A. Bimonte-Nelson; Ronald E. See (Psychopharmacology, 2005)

Combined D1/D2 receptor stimulation under conditions of dopamine depletion impairs spatial working memory performance in humans - Kathryn A. Ellis; Mitul A. Mehta; Keith A. Wesnes; Stuart Armstrong; Pradeep J. Nathan (Psychopharmacology, 2005)

Incidence of novel and potentially archaeal nitrogenase genes in the deep Northeast Pacific Ocean - Mausmi P. Mehta; Julie A. Huber; John A. Baross (Environmental Microbiology, 2005)
Summary Archaea have been detected throughout the oceanic water column and are quantitatively important members of picoplankton in the deep ocean. Two common groups, group I Crenarchaeota and group II Euryarchaeota, are consistently detected in warm hydrothermal fluid and are assumed to have been drawn into the subseafloor, mixed with hydrothermal fluid and then expelled. However, because they remain resistant to cultivation, very little is known about their physiology. Here we show that cold deep‐seawater from the axial valley of Endeavour Segment on the Juan de Fuca Ridge contains not only groups I and II archaea as expected, but also unique potentially archaeal nitrogenase ( nifH ) genes, which are required for nitrogen fixation. These nifH genes are phylogenetically distinct and have dissimilar G+C content compared with those of hydrothermal vent archaea, suggesting that they belong to non‐thermophilic deep‐sea archaea. Furthermore, this sample did not contain mcrA genes, which are present in methanogens, the only known archaeal nitrogen fixers. These nifH genes were not detected in upper water column samples, or in a deep‐seawater sample 100 km away from the spreading axis of the Juan de Fuca Ridge. We propose that these unique nifH genes may be localized to archaea that circulate through the nitrogen‐poor subseafloor at the mid‐ocean ridge as part of their life cycle.

Impact of pharmacometrics on drug approval and labeling decisions: A survey of 42 new drug applications - Venkatesh A. Bhattaram; Brian P. Booth; Roshni P. Ramchandani; B. Nhi Beasley; Yaning Wang; Veneeta Tandon; John Z. Duan; Raman K. Baweja; Patrick J. Marroum; Ramana S. Uppoor; Nam Atiqur Rahman; Chandrahas G. Sahajwalla; et al. (The AAPS Journal, 2005)

The effects of acute tyrosine and phenylalanine depletion on spatial working memory and planning in healthy volunteers are predicted by changes in striatal dopamine levels - Mitul A. Mehta; Deepa Gumaste; Andrew J. Montgomery; Sarah F. B. McTavish; Paul M. Grasby (Psychopharmacology, 2005)

Influence of sex and estrous cyclicity on conditioned cue-induced reinstatement of cocaine-seeking behavior in rats - Rita A. Fuchs; K. Allison Evans; Ritu H. Mehta; Jordan M. Case; Ronald E. See (Psychopharmacology, 2005)

Generation and analysis of expressed sequence tags from the salt-tolerant mangrove species Avicennia marina (Forsk) Vierh. - Preeti A. Mehta; K. Sivaprakash; M. Parani; Gayatri Venkataraman; Ajay K. Parida (Theoretical and Applied Genetics, 2005)

Impaired set-shifting and dissociable effects on tests of spatial working memory following the dopamine D2 receptor antagonist sulpiride in human volunteers - Mitul A. Mehta; Facundo F. Manes; Gianna Magnolfi; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2004)

Attenuation of ischemia/reperfusion induced MAP kinases by N-acetyl cysteine, sodium nitroprusside and phosphoramidon - A. Mehta; C.P.S. Sekhon; S. Giri; J.K. Orak; A.K. Singh (Molecular and Cellular Biochemistry, 2002)

Activation of Raf-1/MEK-1/2/p42/44MAPK cascade alone is sufficient to uncouple LDL receptor expression from cell growth - Gurpreet S. Kapoor; Brett A. Atkins; Kamal D. Mehta (Molecular and Cellular Biochemistry, 2002)

Molecular Cloning and Characterization of Oleoyl-ACP Thioesterase Gene from Brassica juncea - M. N. A. Mandal; I. M. Santha; M. L. Lodha; S. L. Mehta (Journal of Plant Biochemistry and Biotechnology, 2002)

Improved short-term spatial memory but impaired reversal learning following the dopamine D2 agonist bromocriptine in human volunteers - Mitul A. Mehta; Rachel Swainson; Alan D. Ogilvie; Barbara Sahakian; Trevor W. Robbins (Psychopharmacology, 2001)

Nucleoside diphosphate kinase - a component of the [Na + ]- and [Cl - ]-sensitive phosphorylation cascade in human and murine airway epithelium - Treharne K.; Riemen C.; Marshall L.; Muimo R.; Mehta A. (Pflügers Archiv - European Journal of Physiology, 2001)

Production of kavapyrones by Kava (Piper methysticum) tissue cultures - D.P. Briskin; H. Kobayashi; A. Mehta; M.C. Gawienowski; L. Ainsworth; M.A.L. Smith (Plant Cell Reports, 2001)

Systemic sulpiride in young adult volunteers simulates the profile of cognitive deficits in Parkinson's disease - Mitul A. Mehta; B. J. Sahakian; Peter J. McKenna; Trevor W. Robbins (Psychopharmacology, 1999)

Pharmacokinetics and Tissue Disposition in Monkeys of an Antisense Oligonucleotide Inhibitor of Ha-Ras Encapsulated in Stealth Liposomes - Rosie Z. Yu; Richard S. Geary; Janet M. Leeds; Tanya Watanabe; Jonathon R. Fitchett; John E. Matson; Rahul Mehta; Gregory R. Hardee; Michael V. Templin; Ken Huang; Mary S. Newman; Yoli Quinn; et al. (Pharmaceutical Research, 1999)

Inter-decadal modulation of the impact of ENSO on Australia - S. Power; T. Casey; C. Folland; A. Colman; V. Mehta (Climate Dynamics, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Low density lipoproteins and Lovastatin modulate the organ-specific transendothelial migration of primary and metastatic human colon adenocarcinoma cell lines in vitro - Nikhil Mehta; John Hordines; Donald Sykes; Ralph J Doerr; Stefan A Cohen (Clinical & Experimental Metastasis, 1998)

Financial and economic analyses of agroforestry systems and a commercial timber plantation in the La Amistad Biosphere Reserve, Costa Rica - N. G. Mehta; W. A. Leuschner (Agroforestry Systems, 1997)

Interaction of scrapie agent and cells of the lymphoreticular system - R. I. Carp; S. M. Callahan; B. A. Patrick; P. D. Mehta (Archives of Virology, 1994)

Ultrastructure of the cyanobacterium,Mastigocladus laminosus - S. A. Nierzwicki; D. Maratea; D. L. Balkwill; L. P. Hardie; V. B. Mehta; S. E. Stevens (Archives of Microbiology, 1982)